Iatrogenic dissection of the left main coronary artery during elective diagnostic procedures – A report on three cases - Djenić, Nemanja; Džudović, Boris; Romanović, Radoslav; Ratković, Nenad; Jović, Zoran; Djukić, Bosko; Spasić, Marijan; Stojković, Siniša; Obradović, Slobodan (Vojnosanitetski pregled, 2016)
Introduction. Left main coronary artery dissection is a rare and potentially life-threatening complication of coronary angiography and angioplasty which requests urgent revascularization. Case report. During the period between 2010 and November 2014 at single healthcare center we did totally 8,884 coronary procedures, out of which 2,333 were percutaneous coronary interventions (PCI). In this period we had a total of 3 (0,03%) left main coronary artery dissections, and all of them were successfully treated by PCI. We presented three cases with iatrogenic dissection of the left main coronary artery, occurred during elective diagnostic procedures, successfully treated with PCI with different techniques. Conclusion. PCI could be fast and life-saving approach in iatrogenic dissections of the left main coronary artery.